Effect of polypropylene fibers on the California bearing ratio of air cured stabilized tropical peat soil - Kalantari, Behzad; Kim Huat, Bujang; Prasad, Arun (Science Publications, 2010)
Problem statement: Peat soil is well known to deform and fail under a light surcharge load and is characterized with low shear strength, high compressibility and high water content. With the rising demand from the construction industry, utilization of these soils is required and suitable technique needs to be found out for stabilizing them. Approach: Model study had been carried to stabilize peat soil using cement as binding agent and polypropylene fibers as additive. Due to high natural water content of the peat soil, the stabilized peat soil samples were kept at normal room temperature and relative humidity for air curing for 90 days. The improvement in the mechanical strength of the stabilized samples was studied by California Bearing Ratio (CBR) test for both, unsoaked and soaked samples. The water-cement ratio of the samples was measured for 180 days to study the improvement in strength over time. Results: The results of CBR tests showed an increase by a factor over 22 for unsoaked condition and 15 for the soaked condition of the stabilized samples. With the addition of the polypropylene fibers to the stabilized peat soil with cement not only improved the strength of the stabilized peat soil but also contributed to considerable amount of uniformity and intactness to the stabilized peat soil samples. It was also observed that as the curing time for the stabilized peat soil continued through 180 days the moisture content continued to decrease as well. Thus the water-cement (w/c) ratio reduced and as a result of cement hydration, the strength stabilized peat soil samples increased in hardness and gained strength through the curing period. Conclusion/Recommendations: Cement and polypropylene fibers can be used to improve the mechanical strength of the soft peat soil by adopting air curing technique.